Strategi Perpustakaan Dalam Meningkatkan Aksesibilitas Layanan Kepada Anak Tunanetra Di Sekolah Dasar Luar Biasa Negeri (SDLBN) 117709 Kampung Baru Labuhan Batu - Pratiwi, Reni Ayu; Ritonga, Sakti; Syam, Abdi Mubarak (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
This research aims to examine the library tactics used at the State Special Elementary School (SDLBN) 117709 Kampung Baru Labuhan Batu to increase the accessibility of services for blind students, and what challenges the State Special Elementary School (SDLBN) 117709 Kampung Baru Labuhan Batu faces in providing  the service.  This type of research uses a qualitative descriptive research methodology.  The collected data is checked and explained adequately according to the research location.  Purposive sampling was used as a method of collecting information, and the school principal, library manager, and teacher of the blind department were the participants.  Data collection is done by observation, both general and in-depth, and documenting.  The results of this research show that the library's strategy in increasing the accessibility of services to blind children at the State Special Elementary School (SDLBN) 117709 Kampung Baru Labuhan Batu is by carrying out a mobility orientation which will be conveyed to new students, providing information to teachers in each disability department which will later be  delivered by students and utilizing available teaching aids to provide knowledge to blind students.  Meanwhile, the obstacles faced are vandalism, lack of facilities and infrastructure such as computers and programs needed for blind children, lack of teaching aids for blind children and also the braille books provided in libraries still use the old curriculum, namely KTSP, not the new curriculum, namely K13 and librarians who  less professional.